Pengaruh Stressor Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Dealer Yamaha Surya Inti Putra Pahlawan Kota Probolinggo - Anjani, Vika; Elmas, Muhammad Syarif Hidayatullah; Rahajeng, Yekti (Universitas Panca Marga, 2024)
This study aims to determine the effect of Stressor and work motivation on employee performance and to determine the most dominant influence between Stressor and work motivation on employee performance. Quantitative research with causal associative relationships is the type of research used. Stressor (X1) and work motivation (X2) are independent variables. While employee performance (Y) is the dependent variable used in this study. The sample in this study was 34 employees. The determination of the sample used in this study was saturated sampling. The results of the study stated that there was a partial influence of Stressor and work motivation on employee performance because t count> t table (2.252> 1.696), t count> t table (2.049> 1.696). The dominant test results of the stressor variable are variables that have a very large influence on employee performance because the beta coefficient value is 0.362.